2010
DOI: 10.1002/jcp.22405
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mesenchymal stem cells from human normal and hyperplastic gingiva

Abstract: Human gingiva plays an important role in the maintenance of oral health and shows unique fetal-like scarless healing process after wounding. Here we isolate and characterize mesenchymal stem cells from human normal and hyperplastic gingival tissues (N-GMSC and H-GMSC, respectively). Immunocytochemical staining indicated that gingival lamina propria contained Stro-1 and SSEA-4 positive cells, implying existence of putative gingival MSC. Under attachment-based isolating and culturing condition, gingival MSC disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(173 citation statements)
references
References 45 publications
7
161
1
4
Order By: Relevance
“…peroxisome proliferator-activated receptor γ) and chondrogenic markers (i.e. collagen 2A1 and aggrecan) [41][42][43][44] .…”
Section: Deciduous Teeth and Oral Mucosa: Two Promising Reservoir Of mentioning
confidence: 99%
“…peroxisome proliferator-activated receptor γ) and chondrogenic markers (i.e. collagen 2A1 and aggrecan) [41][42][43][44] .…”
Section: Deciduous Teeth and Oral Mucosa: Two Promising Reservoir Of mentioning
confidence: 99%
“…Human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) are valuable resources for cell replacement therapies. Determination of specific markers are required for effective utilization of stem cells and elimination of tumor initiating cells (57). For this purpose, cell surface glycan variations have been investigated to detect the most appropriate markers.…”
Section: Embryonic Stem Cell Sialylated N-glycansmentioning
confidence: 99%
“…These biological properties suggest that MSCs derived from gingiva might possess some intrinsic properties distinct from those of oral mucosa-derived MSCs (Tang et al, 2011). Recent studies have shown that a population of clustered cells in the lamina propria layer of human gingiva displays positive signals for pluripotency-related markers, Oct-4, SSEA-4, and Stro-1 (Zhang et al, 2009;Tang et al, 2011), with some co-expressing Oct-4/SSEA-4 or Oct4/Stro-1 (Zhang et al, 2009). Additionally, the human oral mucosal/gingival lamina propria (OMLP) has been shown to harbor a population of cells positive for lowaffinity neurotrophin (p75), a marker of neural stem cells, organized in cord-like structures that are also positively stained for Oct-4 and Sox2 (Marynka-Kalmani et al, 2010).…”
Section: Gingiva and Oral Mucosa: Expression Of Stem-cell-related Genesmentioning
confidence: 99%
“…Importantly, human oral mucosa-and gingiva-derived MSCs invariably display a higher proliferation rate than do BMSCs (Zhang et al, 2009;Davies et al, 2010;Marynka-Kalmani et al, 2010;Tomar et al, 2010;Tang et al, 2011), which was likely attributed to the constitutive expression of human reverse telomerase transcriptase (hTERT) (Zhang et al, 2009;Davies et al, 2010). Moreover, the in vivo self-renewal capacity of gingiva-derived MSCs has been demonstrated by serial subcutaneous (s.c.) transplantation in immunocompromised mice (Zhang et al, 2009;Tang et al, 2011). These findings support that a population of MSCs with potent self-renewal and proliferative potentials can be readily isolated from human oral mucosa and gingival tissues and reliably expanded ex vivo for large-scale culture.…”
Section: Self-renewalmentioning
confidence: 99%
See 1 more Smart Citation